Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Model Snowball Throwing Mata Pelajaran Bahasa Indonesia Kelas V SDN-4 Kasongan Lama Tahun Pelajaran 2016/2017: Improving Learning Outcomes of Students Through the Application of Snowball Throwing Models in Grade V Indonesian Language Subjects at Kasongan Elementary School-4 Old 2016/2017 Academic Year - Widia Alfisa; Bulkani Bulkani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims: (1) To find out the learning activities of Indonesian Language students in class V by applying the Snowball Throwing learning model. (2) To find out the improvement of Indonesian language learning outcomes of fifth-grade students of Kasongan Lama Elementary School-4 by asking the Snowball Throwing learning model. The type in this study used a variety of classroom action research (CAR). As for the subjects in this study were students of class V SDN-4 Kasongan Lama, amounting to 24 students. The instruments used in this study were observation sheets and test questions about learning outcomes in the form of essays. The data analysis technique used is qualitative and quantitative.